STUDY OF DENDRITIC CELL MIGRATION USING CELL-IQ ANALYSIS SYSTEM - T. L. Nekhaeva; A. B. Danilova; I. A. Baldueva (Сибирский онкологический журнал, 2018)
Dendritic cells (DCs) belong to specialized pool of antigen-presenting cells with high functional plasticity and manifest with immunostimulatory or immunosuppressive potential  depending on sequence and combination of microenvironment stimuli, which determine their  differentiation, maturation and activation. The use of antitumor DCs vaccines is based  on the ability of DCs specifically activated in vitro migrate for antigen presentation to T- lymphocytes. We studied the components of the tumor microenvironment that are capable of inhibiting DCs migration. The study of the mobility of DCs in Cell-IQ experimental  analytical system showed the presence of an inverse correlation of high strength between  the average trajectory speed and the level  of immunosuppressive factors (ISFs) in  supernatants of cultured skin melanoma cells (TGFβ1, IL-10, IL-18, VEGF-A, EGF, FGF, HGF,  sFASL (p<0.01). An inverse relation of high force was found between the movement angle of the DCs population and the expression of cancer testis antigens (CTAs) and other tumor- associated antigens (TAAs) on tumor cells (Melan A, tyrosinase, families of MAGE, BAGE, NY- ESO-1 (p<0.01)). The speed of DCs movement in culture system with melanoma cells #894  was 30.10±2.23 μm/h and differed from that in the presence of IL-10 1 ng/ml (10.45±0.52  μm/h), TGFβ1 10 ng/ml (14.32±0.42 μm/h), VEGF 50 ng/ml (18.7±1.89 μm/h) (p<0.05).  One can assume that content of this ISFs in the blood is one of the factors determining clinical efficacy of DCs immune therapy.